Driving change with evidence and knowledge: Transforming knowledge services for the NHS across England. (March 2020) - Day, Alison; Goswami, Louise
Health Education England (HEE) through its publication of Knowledge for Healthcare (HEE (2014) Knowledge for Healthcare: a development framework for NHS Library and Knowledge Services in England 2015–2020.https://www.hee.nhs.uk/sites/default/files/documents/Knowledge_for_healthcare_a_development_framework_2014.pdf sets out an ambitious vision to transform NHS Library and Knowledge Services at a time of great change for the health service. Five years on this article outlines the key strand of work undertaken to mobilise evidence and organisational knowledge at scale across the health service in England. Using evidence and knowledge is crucial to drive and sustain change and the role of librarians and knowledge specialists is business critical to underpin this service transformation in healthcare. Driver diagrams were used to plan the work to encourage NHS organisations to apply and use evidence, build know-how, continue to learn and drive innovation. Engagement with senior stakeholders was a critical enabler and the impact of the #AMillionDecisions advocacy campaign to highlight the multiple benefits of working with librarians and knowledge specialists is considered. The development of practical tools has supported delivery. These have included a maturity model self-assessment tool to identify opportunities to use evidence and knowledge by senior leaders and updating of the NHS Knowledge Mobilisation Framework e-learning and postcards to enable healthcare staff to use simple knowledge management techniques to share their knowledge and learning. This work was dependent upon developing the skills of existing health librarians and various approaches are described. The article concludes with a reflection on the recommendations from the Topol Review (Topol E (2019) The Topol Review. Preparing the healthcare workforce to deliver the digital future. An independent report on behalf of the Secretary of State for Health and Social Care.https://topol.hee.nhs.uk/wp-content/uploads/HEE-Topol-Review-2019.pdf (accessed 31 January 2020)) to expand the knowledge specialist workforce and outlines future developments planned for the next 5 years and beyond.